2011
DOI: 10.3892/or.2011.1573
|View full text |Cite
|
Sign up to set email alerts
|

Cucurmosin induces apoptosis of BxPC-3 human pancreatic cancer cells via inactivation of the EGFR signaling pathway

Abstract: Abstract. Pancreatic cancer remains the fourth most common cause of cancer-related death in the United States. Potent therapeutic strategies are urgently needed for pancreatic cancer. Cucurmosin is a novel type 1 ribosome-inactivating protein (RIP) isolated from the sarcocarp of Cucurbita moschata (pumpkin). Due to its cytotoxicity, cucurmosin can inhibit tumor cell proliferation through induction of apoptosis on tumor cells, but the specific mechanism is still unclear. We explored the function of cucurmosin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…These studies demonstrated that C . moschata has extensive bioactivities, such as hepatoprotection [ 5 ], anti-diabetes [ 6 ], anti-cancer [ 7 ], and anti-obesity properties [ 8 ]. Although more detailed and clinical studies are needed to confirm the medicinal effects in light of rational bioactivity function, C .…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated that C . moschata has extensive bioactivities, such as hepatoprotection [ 5 ], anti-diabetes [ 6 ], anti-cancer [ 7 ], and anti-obesity properties [ 8 ]. Although more detailed and clinical studies are needed to confirm the medicinal effects in light of rational bioactivity function, C .…”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of IL-1β have a detrimental effect on pregnancy, leading to complications such as chorioamnionitis, preeclampsia, and preterm birth [47][48][49][50]. CMD has been widely used in traditional herbal remedies and foods and has received considerable attention due to its extensive bioactivity as an anti-diabetic [51], anti-cancer [52], anti-obesity [53], and anti-inflammatory agent [35]. However, the efficacy of TCMD has not been fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their antimutagenic and immunomodulatory activity, pumpkin seeds have also been associated with lower risk of gastric, breast, lung, prostate and colorectal cancers (6,17,19,20). The ribosome-inactivating proteins Moschatin and Cucurmosin from the mature seeds of pumpkin (C. moschata) were reported to inhibit melanoma cell proliferation as well as leukemia, lung adenocarcinoma and pancreas cancer cell proliferation for the latter (21)(22)(23). Pumpkin albumin 2 S was shown to exhibit a strong anticancer activity toward breast adenocarcinoma (MCF-7), ovarian teratocarcinoma (PA-1), prostate cancer (PC-3 and DU-145) and hepatocellular carcinoma (HepG2) cell lines (17).…”
Section: Medicinal Bioactivities Of Pumpkin Seedsmentioning
confidence: 99%